2014
DOI: 10.1111/gcb.12576
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon stock change following afforestation in Northern Europe: a meta‐analysis

Abstract: Northern Europe supports large soil organic carbon (SOC) pools and has been subjected to high frequency of land-use changes during the past decades. However, this region has not been well represented in previous large-scale syntheses of land-use change effects on SOC, especially regarding effects of afforestation. Therefore, we conducted a meta-analysis of SOC stock change following afforestation in Northern Europe. Response ratios were calculated for forest floors and mineral soils (0-10 cm and 0-20/30 cm lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
134
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(150 citation statements)
references
References 73 publications
12
134
3
1
Order By: Relevance
“…It was similar to most published studies (such as Jafarian and Kavian, 2013;Zhang et al, 2013;Gelaw et al, 2014). This phenomenon may be caused by thefact that forest has more SOC, origining from surface litter input, than cultivated land (Bárcena et al, 2014). Additionally, different soil properties and decomposition rate of different land use types in surface soil may affect SOC and STN (Table 2; Jafarian and Kavian, 2013).…”
Section: Soc and Stn Concentrations And Stocks Across Land Usessupporting
confidence: 85%
See 1 more Smart Citation
“…It was similar to most published studies (such as Jafarian and Kavian, 2013;Zhang et al, 2013;Gelaw et al, 2014). This phenomenon may be caused by thefact that forest has more SOC, origining from surface litter input, than cultivated land (Bárcena et al, 2014). Additionally, different soil properties and decomposition rate of different land use types in surface soil may affect SOC and STN (Table 2; Jafarian and Kavian, 2013).…”
Section: Soc and Stn Concentrations And Stocks Across Land Usessupporting
confidence: 85%
“…Under the changes in land management, soil has historically played the roles of both source and sink of carbon (Torbert et al, 1997). Specifically, it has been well demonstrated that the SOC stock of ecosystem was significantly affected by the land use/cover change especially to agriculture activities (Wu et al, 2003;Gelaw et al, 2014;Gao et al, 2015), deforestation (Kucuker et al, 2015;Fujisaki et al, 2015), afforestation (Bárcena et al, 2014;Omonode and Vyn, 2006). As a summary, most of these studies have largely focused on SOC variability under different land uses and soil depth in horizon and vertical layers.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation restoration from cropland into woodland, shrubland, and grassland has been recognized as an effective strategy for SOC stock and distribution (Bárcena et al, 2014;Deng et al, 2014;Zhu et al, 2014;Wang et al, 2014). However, natural vegetation restoration is distinctly different from the artificial approach in terms of management (Del Galdo et al, 2003;Six et al, 2000), microclimate (temperature and moisture) (Laganière et al, 2010), species composition , soil properties (Xu et al, 2014), and fine root quantity and quality (Solly et al, 2014), thus resulting in significantly different SOC stock and distribution (Jin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the literature have considered the SOC change as a result of land-use transition, within the context of a national or a regional sampling scheme (Callesen et al 2003), as a meta-analysis (Poeplau et al 2011, Bárcena et al 2014, or as a national assessment within a single land use transition (Davis and Condron 2002). The assessment of the significance of the SOC change resulting from of all possible land-use transitions is methodologically difficult, because individual studies frequently do not provide the information required to carry out the required calculations (Bretz et al 2010).…”
Section: Comparison With Other Workmentioning
confidence: 99%